Pengaruh variabel fulmer h-score terhadap harga saham pada Badan Usaha Milik Negara Non Bank di Bursa Efek Indonesia periode 2013-2017 - Ivo Rolanda; Mia Laksmiwati (Penerbit Goodwood, 2020)
Purpose: This study aims to find out the influence of fulmer variables, namely retained earning / total assets, sales / total assets, earning before tax / equity, cash flow / total debt, total debt / total asset, current liabilities / total asset, log tangible asset, working capital / total debt, and log EBIT / interest on stock prices. Research methodology: The data in this study were secondary data in the form of financial statements of SOE companies. The calculation used Microsoft Excel 2010. The program used to analyze data was the Econometric Views 9 (EViews 9) program. Statistical testing was performed at a 95% confidence level and 5% significance level. From the 20 BUMN companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017, 12 companies were sampled. Results: Variable Retained Earning / Total Assets, Earning Before Taxes / Equity, Cash Flow / Total Debt and Current Liabilities / Total Assets affect the stock price, while Sales / Total Asset variables, Total Debt / Total Assets, Log Tangible Asset, Working Capital / Total Debt and Log Earning Before Interest and Tax / Interest have no effect on the share prices of non-bank SOEs on the Indonesia Stock Exchange in the period 2013-2017 period. Limitations: Historical data used were limited to time periods, 5 year time series data for the period 2013 - 2017 and the variables used were only nine variables. Contribution: Non-bank SOEs must pay attention to ratios that have not influenced their share prices, such as TATO, DER, Tangible Assets, WCTD and TIER. This shows that SOEs’ assets have not been used productively, especially Tangible Assets. The suboptimal level of efficiency can be seen from the achievement of low income so that the ability of operating profit to cover interest expenses is still low. Keywords: Fulmer model, Stock price, Non-bank BUMN